Fulfillment of Children's Health Rights in Ambon City During The Covid 19 Pandemic - Veriena Joseva B Rehatta; Wilshen Leatemia; Tomy Palijama (Faculty of Law, Universitas Pattimura, 2021)
Many challenges that can affect children's health, including access to health services, health disparities, social, cognitive, and emotional factors both in the family and society, environmental factors, especially poverty, and of course the Covid-19 virus are the main problems today. This study aims to see how the role of ambon city government in dealing with health problems in children during the Covid-19 pandemic and how the role and responsibility of the community in looking at health development in children during the Covid-19 pandemic. This research was conducted using a juridical approach emperis which is a descriptive study of qualitative analysis. The research seeks to illustrate how the Fulfillment of Children's Health Rights in Ambon City During the Covid-19 Pandemic. The workings of empirical juridical or sociological juridical methods in this research proposal are from the results of the collection and discovery of data and information through literature studies on the assumptions or basic assumptions used in answering the problems in this research, then conducted inductive-verifikative testing on the latest facts contained in society. The results of this study indicate that in the handling of the Covid-19 Pandemic children in Ambon, it went well according to the Health protocol, as well as the services provided by the health officers at the puskesmas and the Ambon City Health Service to the exposed children, all were examined and treated properly. But there are also parents who do not bring their children to do an examination if they feel symptoms of Covid-19. Therefore, the status of being exposed to Covid-19 in children is not so much because of the fear of parents to have their children checked.